Ultrafiltration Technology for Batik SME Wastewater Treatment: Column-Based Materials with Zippers for Plant Irrigation Water Supply - Zakia, Maulida; Mahatmanti, F. Widhi; Wati, Safna Rahma; Rahmalia, Berliana Putri; Rengga, Wara Dyah Pita (Universitas Negeri Semarang, 2024)
Textile batik wastewater discharged into drains can contaminate groundwater and harm ecosystems and human health. This study focuses on reducing hazardous heavy metals in sewage through physical and chemical filtration. Heavy metals in the wastewater can poison aquatic organisms, disrupt food chains, and contaminate water sources. The goal is to analyze the heavy metal content, pH, and colour of batik wastewater to make it safe for plant irrigation. The filtration process uses silica sand, activated carbon, and zeolite for mechanical filtration and ion exchange. Ultrafiltration is added to remove fine particles, heavy metals, and organic matter more effectively while resisting fouling. These materials are placed in zipper bags for easy replacement and regeneration. The wastewater passes through a filtration column consisting of two tanks: Tank 1 for fresh wastewater and sedimentation, and Tank 2 for overflow from Tank 1. Tests were conducted for Cr, Cu, Pb, and Zn using AAS, pH with a universal pH meter, and colour through organoleptic analysis. Cr levels initially exceeded quality standards, while Cu, Pb, and Zn were within safe limits. After filtration, reductions of Cr, Cu, Pb, and Zn were 81%, 8%, 22%, and 85%, respectively. The pH decreased from 10–11 to 7–8, and water color improved from murky greenish-brown to clearer. The results demonstrate the potential of ultrafiltration in reducing heavy metals, stabilizing pH, and improving water clarity. Wastewater treated through this process meets safety standards and can be used for plant irrigation.